2022
DOI: 10.1530/erc-21-0085
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of GATA2 in prostate cancer by a clinically available small molecule

Abstract: Castration-resistant prostate cancer (CRPC) remains highly lethal and in need of novel, actionable therapeutic targets. The pioneer factor GATA2 is a significant prostate cancer (PC) driver and linked to poor prognosis. GATA2 directly promotes androgen receptor (AR) gene expression (both full-length and splice-variant) and facilitates AR binding to chromatin, recruitment of coregulators, and target gene transcription. Unfortunately, there is no clinically applicable GATA2 inhibitor available at the moment. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 70 publications
(138 reference statements)
0
4
0
Order By: Relevance
“…3; Supplementary Data9). Similarly, we also highlighted key TFs, NKX3-1 (66-69) and GATA2 (70)(71)(72)(73) for prostate cancer (Supplementary Data10).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…3; Supplementary Data9). Similarly, we also highlighted key TFs, NKX3-1 (66-69) and GATA2 (70)(71)(72)(73) for prostate cancer (Supplementary Data10).…”
Section: Discussionmentioning
confidence: 86%
“…3; Table S9). Similarly, we also highlighted key TFs, NKX3-1 [62][63][64][65] and GATA2 [66][67][68][69] for prostate cancer (Table S10). Unfortunately, we did not observe significant TFs in lung cancer, likely due to the less genetic effects of the TF on downstream regulated genes 38 .…”
Section: Discussionmentioning
confidence: 87%
“…GATA2 could promote PCa progression in an AR-dependent manner, embodied in facilitating the expression of AR and AR target gene, which was also considered to function as a pioneer factor [ 51 , 52 ]. In addition, GATA2 was involved in the development of CRPC and metastatic PCa [ 53 ] through directly upregulating a battery of target genes, such as BMP6, EZH2, FOXM1 and IGF2, which were associated with PCa metastasis and taxane resistance [ 26 , 54 , 55 ]. Our current study indicated that ST6GALNAC5 may also contribute to the oncogenic effects of GATA2 to promote PCa cell invasion.…”
Section: Discussionmentioning
confidence: 99%
“…K7174 also significantly reduces tumor growth in a murine xenograft model of CRPC (48). Dilazep, a vasodilator that is used to treat patients with hypertension, cardiovascular, and renovascular disorders, is a second pharmaceutical agent that blocks GATA2 DNA-binding, suppresses the expression of AR, and reduces tumor growth in a murine xenograft model of CRPC (50). These therapeutic options have not yet been tested clinically for men with prostate cancer, however.…”
Section: Gata2 and The Armentioning
confidence: 99%